Student Perceptions of Higher Education and Apprenticeship Alignment - Douglas Decker (MDPI AG, 2019)
Since its inception in medieval Europe, apprenticeships have played a vital role in knowledge transfer from one generation to the next. In a mutually beneficial relationship, the master craftsman passes along years of skill and wisdom to the younger apprentice while gaining the youthful, energetic infusion of labor from the burgeoning new learner. In the 21st century, the concept remains largely unchanged, but after years of falling by the wayside, the United States is experiencing a renaissance in the apprenticeship movement. For generations, apprenticeships were marginalized in favor of a more traditional form of classroom-based education now termed Career and Technical Education. However, with economic changes activated by a national ‘skills gap’ and a retiring Baby Boomer generation, the country faces a potential crisis if a skilled workforce is not trained quickly. With just over 500,000 participants nationally, apprenticeship pales in comparison to the 17 million students currently enrolled in higher education. Some of the fastest growing sectors of the American economy such as Science, Technology, Engineering and Math (STEM), and healthcare, have only a few thousand apprentices each. The solution to this challenge lies with the alignment of both methodologies. This article explores the subject of integrating apprenticeship growth and the higher education sector.